Crystalline semiconducting inorganic materials - Lee, Fu Min. (2011)
Metal Chalcogenide materials have shown potential in enhancing laser devices given its properties such as high non-linear optical (NLO). The purpose is to develop a metal chalcogenide material with high NLO properties. The synthesis and crystal structure of a new noncentrosynmmetric compound Hg7InS6Cl5 are reported. Hg7InS6Cl5 is crystallized using high temperature solid state synthesis and are in the triclinic space group P1. The unit cell parameters are a = 7.3500 (15) , b = 10.420 (2) , c = 13.720 (3) , Z = 4. The crystal features a three-dimensional frame work with Hg atom emerge in 8 different coordination geometrics and In atoms surrounded by 6 S atoms. The Hg and In structures surrounded the corners to form the 3 dimensional framework. The crystal structure showed unequal length and are not mutually orthogonal. This will be an advantage towards NLO properties presence in the crystal. Further work is to be done to have a purify crystal in order to test the optical properties.